2020
DOI: 10.21037/atm-20-4901
|View full text |Cite
|
Sign up to set email alerts
|

Improved osteogenic activity and inhibited bacterial biofilm formation on andrographolide-loaded titania nanotubes

Abstract: Background: Delivery of local drugs with a titania nanotube is an attractive approach to combat implantrelated infection. Our earlier study has confirmed that nanotubes loaded with gentamicin could significantly improve the antibacterial ability. On this basis, the used andrographolide in this paper has a high antibacterial activity, which cannot only avoid the evolution of antibiotic-resistant bacteria but also has simultaneously excellent biocompatibility with osteogenic cells.Methods: Two mg of andrographol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Compared with free andrographolide, the nanocrystals prepared by solvent diffusion method displayed a better aqueous solubility and intestinal permeability, as well as obvious protective effect on paracetamol‐induced liver injury at lower dosage, which this work emphasized that nanocrystalline technology can be regarded as a platform to avoid the limitations of andrographolide (Basu et al, 2020). In addition to the above, nanomicelles (Mishra et al, 2017), nanovesicles (Sanati, Chua, Nasiri, & Hashemi, 2020) and carbon nanotubes (Feng et al, 2020) are also committed to improving the pharmaceutical properties of andrographolide. In brief, future projects may reap huge fruits from accurate, sufficient and effective delivery of andrographolide, which will be conducive to overcome the shortage of clinical transformation of this plant‐based bioactive compound.…”
Section: Pharmaceutical Researches Of Andrographolidementioning
confidence: 99%
“…Compared with free andrographolide, the nanocrystals prepared by solvent diffusion method displayed a better aqueous solubility and intestinal permeability, as well as obvious protective effect on paracetamol‐induced liver injury at lower dosage, which this work emphasized that nanocrystalline technology can be regarded as a platform to avoid the limitations of andrographolide (Basu et al, 2020). In addition to the above, nanomicelles (Mishra et al, 2017), nanovesicles (Sanati, Chua, Nasiri, & Hashemi, 2020) and carbon nanotubes (Feng et al, 2020) are also committed to improving the pharmaceutical properties of andrographolide. In brief, future projects may reap huge fruits from accurate, sufficient and effective delivery of andrographolide, which will be conducive to overcome the shortage of clinical transformation of this plant‐based bioactive compound.…”
Section: Pharmaceutical Researches Of Andrographolidementioning
confidence: 99%
“…Bacteria that attach to a surface and grow as biofilms are protected from antibiotic-induced killing. In addition, reduced antibiotic susceptibility contributes to the persistence of biofilm infections, forming a vicious cycle ( Feng et al, 2020 ). This result explains why MRSA has acquired resistance to practically all antibiotics developed for clinical use in the past 50 years, including vancomycin (Van), which is the last resort to treating MRSA infection ( Howden et al, 2010 ; McGuinness et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…AG exhibits potential antibacterial activity against most Gram-positive bacteria, among which MRSA is the most sensitive to AG ( Banerjee et al, 2017 ). More importantly, AG significantly inhibits biofilm formation without cytotoxicity ( Feng et al, 2020 ). It works by inhibiting virulence factors and the quorum sensing (QS) system, an intercellular communication mechanism closely related to biofilm formation, stability, and development ( Solano et al, 2014 ; Castillo-Juarez et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns exist over the efficacy of surfacebound antibiotics, including their limited interaction range relative to their bound position, their effectiveness against only specific bacteria, and the potential for bacterial resistance [49,[105][106][107][108][109]. Titanium nanotubes (NT) have been utilised as carriers of bactericidal chemicals coupled with the enhanced osseointegration found with titanium nanotube surfaces [110]. Gentamicin-charged nanotubes can significantly improve anti-bacterial capacity and encourage increased osteoblastic functionality, but again, concerns exist over antibiotic resistance associated with the use of depot antimicrobials [111].…”
Section: Inorganic Moleculesmentioning
confidence: 99%
“…Other organic ASM molecules including chlorhexidine, chloroxylenol, and polyhexamethylenebiguanide have been shown to be efficacious and may potentially avoid drug resistance [49]. Titanium nanotubules can be loaded with andrographolide, a tradition herbal medicine with known anti-inflammatory properties as well as more recently demonstrated anti-bacterial properties; in one study, the nanopatterning demonstrated biocompatibility, increasing the proliferation of mesenchymal stem cells on the surface as well as limited anti-biofilm activity, but the andrographolide-loaded NT inhibited biofilm formation, which was likely by the elimination of free floating bacteria in suspension, by the local andrographolide release, prior to surface attachment over the time period of the in vitro study [110]. The use of sphingosine, a naturally occurring amino alcohol, was investigated as a surface coating for steel and titanium wires, which significantly reduced bacterial adhesion, demonstrated bacterial colonisation, and significantly reduced biofilm formation on implant surfaces with concentrations greater than 5 µM [112].…”
Section: Inorganic Moleculesmentioning
confidence: 99%